2021
DOI: 10.3390/jcm10050933
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sectional Association between Hypercholesterolemia and Knee Pain in the Elderly with Radiographic Knee Osteoarthritis: Data from the Korean National Health and Nutritional Examination Survey

Abstract: Few studies have reported the relationship between knee pain and hypercholesterolemia in the elderly population with osteoarthritis (OA), independent of other variables. The aim of this study was to reveal the association between knee pain and metabolic diseases including hypercholesterolemia using a large-scale cohort. A cross-sectional study was conducted using data from the Korea National Health and the Nutrition Examination Survey (KNHANES-V, VI-1; 2010–2013). Among the subjects aged ≥60 years, 7438 subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…By activating lecithin cholesterol acyltransferase, ApoA1 facilitates the transportation and metabolism of cholesterol in the liver, thereby impeding the onset of hypercholesterolemia. 43 Given that hypercholesterolemia represents a risk factor for OA, 44 the likelihood of developing KOA escalates as the levels of ApoA1 decrease.…”
Section: Discussionmentioning
confidence: 99%
“…By activating lecithin cholesterol acyltransferase, ApoA1 facilitates the transportation and metabolism of cholesterol in the liver, thereby impeding the onset of hypercholesterolemia. 43 Given that hypercholesterolemia represents a risk factor for OA, 44 the likelihood of developing KOA escalates as the levels of ApoA1 decrease.…”
Section: Discussionmentioning
confidence: 99%
“…Statins are amongst the most widely used medications in the treatment of hypercholesterolemia. Prior studies have shown the association between hypercholesterolemia and osteoarthritis [ 27 ]. However, the impact of statins in osteoarthritis remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Statins are commonly used to treat hypercholesterolemia and may have a role in neck pain conditions. Hypercholesterolemia is associated with degenerative musculoskeletal conditions such as osteoarthritis 17–20. However, the use of statins in osteoarthritis remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Hypercholesterolemia is associated with degenerative musculoskeletal conditions such as osteoarthritis. [17][18][19][20] However, the use of statins in osteoarthritis remains unclear. Statin-induced myalgia is a well-known side effect, yet some clinical studies have found that statin use improved radiographic and clinical osteoarthritis symptoms such as pain.…”
Section: Discussionmentioning
confidence: 99%